HISTOPATHOLOGICAL STUDIES ON INTESTINE OF GALLUS DOMESTICUS INFECTED WITH CESTODE PARASITES - S. D. PATIL,; HEMLATA S. CHAUDHARI (WANKHEDE), (The Bioscan, 2011)
The cestode parasites Raillietina corvina and Choanotaenia sp. found infected to the avian host Gallus domesticus. Histopathological studies have been made to assess the extent of damage caused by the parasites. It includes destruction and extrusion of intestinal villi, inflammatory fibrosis due to cysts. Raillietina corvina heavily destroyed, rupturing the villi, piercing through submucosa. So the scolex of Raillietina corvina is penetrative type (Shinde and Mitra, 1980). The extent of damage is proportional to the penetration of scolex. Cysts found encircled with connective tissue sheath deep in the submucosa. Scolex of Choanotaenia sp. is penetrative type as two scoleces found deeply pierced in submucosa of intestine